Impact Evaluation of the Act-Belong-Commit Mental Health Promotion Campaign - Anwar McHenry, Julia; Donovan, Robert; Jalleh, Geoffrey; Laws, Amberlee (Pier Professional Ltd., 2012)
Purpose – Act-Belong-Commit is a community-based positive mental health promotion campaign that targets individuals to engage in activities that enhance their mental health while targeting community organisations that provide such activities to promote their activities under the banner of the Act-Belong-Commit message. This paper aims to detail key findings from a population impact evaluation of the campaign conducted in 2010.Design/methodology/approach – Computer-assisted telephone interviews (CATI) were conducted on a randomly selected adult sample (n=1,113) using quotas to obtain equal representation by age and gender. The questionnaire contained items gauging campaign reach, the impact of the campaign on individual beliefs and behaviours, and perceived societal impact of the campaign on mental illness stigma and openness to mental health issues.Findings – The campaign reached 75 per cent of the population. Amongst those exposed to the campaign, 25 per cent reported changing the way they thought about mental health and mental illness, and 20 per cent reported some behaviour change. The campaign was perceived to be effective in making people more open about mental health issues (77 per cent of reached respondents) and reducing stigma surrounding mental illness (68 per cent of reached respondents).Practical implications – The campaign provides a framework for increasing mental health literacy on a population scale.Originality/value – With its focus on the positive aspects of mental health, the paper shows that the campaign is unique in promoting behaviours that people can and should do to build and maintain good mental health, while also encouraging community organisations and groups that provide mentally healthy activities to partner with the campaign to make mental health “everybody's business”.